Cell Adhesion: The Role of Titanium Surface Nanostructuring on Preosteoblast Morphology, Adhesion, and Migration (Adv. Healthcare Mater. 15/2017). Issue 15 (9th August 2017) - Zhukova, Yulia; Hiepen, Christian; Knaus, Petra; Osterland, Marc; Prohaska, Steffen; Dunlop, John W. C.; Fratzl, Peter; Skorb, Ekaterina V.
Abstract : A kaleidoscope of surface properties guides a kaleidoscope of cell dynamic behavior and communication with a nanoarchitectured support. In article number1601244, Peter Fratzl and co‐workers focus on the impact of different titania nanotopography on osteo‐progenitor cell adhesion, stress fiber formation and migration.